Relationships between different trends of the Mediterranean diet and cardiovascular disease-related risk factors in China: results from the CHNS study, 1997–2009 - Bao, Zhengyang; Qian, Zhengtao; Chen, Jiale; Chen, Yu; Li, Na; Ye, Yang; Ren, Yongwei; Tang, Yiming; Chen, Daozhen (Frontiers in Nutrition, 2024)
Objectives The present study aimed to explore the associations between Mediterranean diet trajectories (MDTs) and cardiovascular disease-related risk factors in Chinese adults. Methods A total of 4,332 participants from the China Health and Nutrition Survey (CHNS) were included in this study. A group-based trajectory model (GBTM) was used to explore Mediterranean diet trajectories (MDTs). Linear regression analyses were conducted to assess the association between Mediterranean diet trajectories and cardiovascular disease-related risk factors. Stratified analyses by gender were also performed. Results The following four groups were identified in the total population: Group 1 (Persistently low MDT, n = 292, 6.74%), Group 2 (Descent MDT, n = 537, 12.40%), Group 3 (Ascent MDT, n = 454, 10.48%), and Group 4 (Persistently high MDT, n = 3,049, 70.38%). Compared to the persistently low MDT (Group 1), both Group 2 and Group 4 were negatively related to low-density lipoprotein cholesterol (LDL-C) (Group 2: β = −0.23, 95% CI: −0.36 to −0.09, p = 0.001; Group 4: β = −0.25, 95% CI: −0.37 to −0.14, p < 0.001), total cholesterol (TC) (Group 2: β = −0.18, 95% CI: −0.32 to −0.04, p = 0.010; Group 4: β = −0.31, 95% CI: −0.43 to −0.19, p < 0.001), and uric acid (UA) (Group 2: β = −15.16, 95% CI: −28.66 to −2.56, p = 0.019; Group 4: β = −27.51, 95% CI: −38.77 to −16.25, p < 0.001) after adjusting for potential risk factors. Only Group 4 exhibited a negative relationship with triglycerides (TG) (β = −0.18, 95% CI: −0.34 to −0.02, p = 0.028) and blood glucose (β = −0.19, 95% CI: −0.37 to −0.02, p = 0.032). Conclusion Four MDTs were identified among the total participants, including men and women. These trajectories were summarized as persistently low MDT, ascent MDT, descent MDT, and persistently high MDT. Adherence to high MDTs could reduce the level of some CVD-related risk factors. The impact of the remote MD on CVD-related risk factors may be greater than that of the proximal MD.